Implementation of the Tahfidz Program in Strengthening the Character Values of MTSN Students in Madiun - Fadeli, Fadeli; Maksum, Muh. Nur Rochim; Mustofa, Triono Ali (International Journal of Education Research and Development, 2026)
This study aims to analyze the implementation of the tahfidz program in strengthening student character values in MTsN 3 Madiun and MTsN 2 Madiun. The research uses a qualitative paradigm with a type of field research and a phenomenological approach. Data was collected through in-depth interviews, non-participant observations, and documentation with informants consisting of madrasah heads, tahfidz teachers, PAI teachers, students, and parents. Data analysis uses interactive model analysis, while data validity is carried out through triangulation and member check. The results of the study show that the two madrassas have different but equally effective tahfidz program implementation models in shaping the Qur'ani character of students. MTsN 3 Madiun implements a religious habituation approach through school culture that emphasizes examples, worship routines, and flexible tahfidz activities, while MTsN 2 Madiun implements a more structured program system with memorization targets, monitoring through mutaba'ah books, tasmi' evaluation, and parental involvement. Character internalization takes place through three dimensions of character according to Thomas Lickona, namely moral knowing, moral feeling, and moral action. The main supporting factors include religious leadership, teacher commitment, and a conducive school environment, while inhibiting factors include differences in students' abilities, academic burden, and psychological pressure from a strict evaluation system.